2012
DOI: 10.1021/la301442f
|View full text |Cite
|
Sign up to set email alerts
|

Versatile Supramolecular Gelators That Can Harden Water, Organic Solvents and Ionic Liquids

Abstract: We developed novel supramolecular gelators with simple molecular structures that could harden a broad range of solvents: aqueous solutions of a wide pH range, organic solvents, edible oil, biodiesel, and ionic liquids at gelation concentrations of 0.1-2 wt %. The supramolecular gelators were composed of a long hydrophobic tail, amino acids and gluconic acid, which were prepared by liquid-phase synthesis. Among seven types of the gelators synthesized, the gelators containing L-Val, L-Leu, and L-Ile exhibited hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
102
0
1

Year Published

2015
2015
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(115 citation statements)
references
References 44 publications
(93 reference statements)
4
102
0
1
Order By: Relevance
“…Depending on the nature of gelator, gel electrolytes can be classified into polymer gel electrolytes [1][2][3][4][5][6][7][8][9][10][11][12][13][14] and low molecular weight gel electrolytes [15][16][17][18][19][20][21][22][23][24][25][26][27][28]. The former are in most of the cases the chemical gels formed as a result of polymerization reactions and chemical bonding.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Depending on the nature of gelator, gel electrolytes can be classified into polymer gel electrolytes [1][2][3][4][5][6][7][8][9][10][11][12][13][14] and low molecular weight gel electrolytes [15][16][17][18][19][20][21][22][23][24][25][26][27][28]. The former are in most of the cases the chemical gels formed as a result of polymerization reactions and chemical bonding.…”
Section: Introductionmentioning
confidence: 99%
“…The latter ones are always physical gels formed by the self-assembly of low molecular weight gelators (LMWGs) in liquid media (solution of electrolytes or ionic liquids) through the intermolecular interactions such as hydrogen bonding, p-p stacking, van der Waals and electrostatic interactions, coordination, or charge transfer. As a result of such interactions a three dimensional network of LMWGs aggregates is formed which adsorbs (incorporates) solvent into its structure [15][16][17][18][19][20][21][22][23][24][25][26][27][28]. The low molecular weight gel electrolytes are thermoreversible.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Basically,i onogels can be prepared by additiono f1 )low molecular weights upramolecular gelators, 2) polymers, or 3) inorganic particles( SiO 2 nanoparticles, metal/metal oxide nanoparticles, carbon nanotubes, etc.). [4] Amongt hese,s upramolecular gelators appeart ob ee specially efficient, since they have the smallest influence on ion dynamics upon confinement.I tw as shown that the gelation of ILs by gelators basedo na mino acids, [5][6][7] urea and amides, [8] carbene complexes, [9] and other amide derivates [10,11] results in ionogelsw ith ionic conductivities slightly lower than those of pure ILs. Moreover,t he gelation of ILs by supramolecular gelators is at hermoreversible process that enables the preparation of ionogels with temperature-controlled sol-gel transitions.…”
Section: Introductionmentioning
confidence: 99%
“…The most important part of the gel electrolyte system is the gelator, depending on its nature, the polymer gel electrolytes [12][13][14][15][16][17][18][19][20][21][22][23][24][25] and low molecular weight gel electrolytes [26][27][28][29][30][31][32][33][34][35][36][37][38][39] can be distinguished. Polymer gels are formed as a result of polymerization reactions and chemical bonding resulting in high thermal stability but no thermal reversibility.…”
Section: Introductionmentioning
confidence: 99%